2002
DOI: 10.1002/j.1551-8833.2002.tb09408.x
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic and Biotic Perchlorate removal in an activated carbon filter

Abstract: Granular activated carbon (GAC) filtration experiments demonstrated that perchlorate was removed by ion exchange rather than by chemical reduction. A column ion‐exchange capacity of 0.172 mg perchlorate per g GAC was calculated. Batch tests confirmed that ion exchange was the dominant mechanism of perchlorate removal by GAC. When influent dissolved oxygen (DO) was 2.5 mg/L and an electron donor solution was supplied, efficient reduction of 50 μg/L perchlorate was achieved using biologically active carbon (BAC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Nitrate has been found to have different effects on perchlorate removal rates. Nitrate has inhibited the perchlorate reduction rate in some studies (Herman and Frankenberger, 1999;Brown et al, 2002) but not in others (Burns et al, 2001;Logan and LaPoint, 2002). A PRB isolate, perc1ace, was able to completely remove perchlorate (130 mg/L) and to simultaneously remove more than 95% of the nitrate (20 mg/L) in a sand-packed bioreactor (Herman and Frankenberger, 1999).…”
Section: Effects Of Nitrate On Perchlorate Removalmentioning
confidence: 96%
“…Nitrate has been found to have different effects on perchlorate removal rates. Nitrate has inhibited the perchlorate reduction rate in some studies (Herman and Frankenberger, 1999;Brown et al, 2002) but not in others (Burns et al, 2001;Logan and LaPoint, 2002). A PRB isolate, perc1ace, was able to completely remove perchlorate (130 mg/L) and to simultaneously remove more than 95% of the nitrate (20 mg/L) in a sand-packed bioreactor (Herman and Frankenberger, 1999).…”
Section: Effects Of Nitrate On Perchlorate Removalmentioning
confidence: 96%
“…This corresponds to an empty bed contact time of 23.5 min. The BAC reactor was seeded using biomass collected from two other BAC reactors: one had been fed Urbana (IL) tap water amended with acetate at a concentration of 2 mg/L as C and 50 μg/L perchlorate (Brown et al, 2002), the other had been fed Urbana groundwater amended with 50 μg/L perchlorate (Lin, 2004). Sorption capacities of the GAC for perchlorate and oxygen were exhausted before initial start-up by recirculating water containing 50 μg/L of perchlorate and saturated by oxygen through the reactor.…”
Section: Reactor Setup and Influent Compositionmentioning
confidence: 99%
“…Biological removal of perchlorate has been evaluated in biofilm reactors using different carrier media including plastic (Min et al, 2004), sand (Min et al, 2004), Celite (Losi et al, 2002), and granular activated carbon (GAC) (Brown et al, 2002) for fixed bed reactors, and sand and GAC for fluidized bed reactors (McCarty and Meyer, 2005;Sutton, 2006). Other reactor configurations include membrane diffuser biofilm reactors (Nerenberg et al, 2002) and ion exchange membrane bioreactor (Matos et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that biological treatment is an effective technology to remove perchlorate from drinking water (Brown et al, 2002;Giblin et al, 2000;Herman and Frankenberger, 1999;Min et al, 2004). For example, for a typical groundwater concentration of 50 μg/L, biologically active carbon (BAC) fixed bed reactors consistently removed perchlorate to below 2 μg/L (Brown et al, 2002(Brown et al, , 2005. Despite these encouraging studies, the reliability of biological drinking water treatment is sometimes questioned, in particular under dynamic loading conditions and during changes in reactor operation, such as after backwashing (Kim and Logan, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Regular backwashing is a key process for fixed bed biofilm reactors that is necessary to prevent clogging, to reduce excessive head loss across the filter, to maintain an active biofilm, to prevent the proliferation of filamentous bacteria and eukaryotic organisms, such as fungi and protozoa, and to enhance the mass transfer of contaminants to the biofilm (Brown et al, 2002;Hozalski and Bouwer, 1998;Laurent et al, 2003). However, backwashing also reduces the amount of active biomass in the reactor, which could potentially lead to unstable reactor performance (Lahav et al, 2001;Nakhla and Farooq, 2003).…”
Section: Introductionmentioning
confidence: 99%